2008
DOI: 10.1097/ijg.0b013e3181666595
|View full text |Cite
|
Sign up to set email alerts
|

Ex-PRESS Glaucoma Shunt Dislocation Into the Anterior Chamber

Abstract: We report a case of an 84-year-old man who had an Ex-PRESS R-50 glaucoma shunt placed under a scleral flap in his right eye for primary open angle glaucoma and uncontrolled intraocular pressure. Twenty-one days after placing the implant, the patient returned with a dislocated shunt resting in the inferior angle of the anterior chamber. Corrected vision was 20/30 with an intraocular pressure of 13 mm Hg. There was no anterior chamber inflammation and no evidence of corneal decompensation. To our knowledge, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…18,19 Because the conjunctiva alone is insufficient to control the initial aqueous flow during the early postoperative period, implantation under a scleral flap is currently recommended to prevent conjunctival erosion and to increase resistance to aqueous outflow in the immediate postoperative period. 20 Despite a number of studies that support the safety and efficacy of the subscleral technique, 21,22 complications include hyphema, transient hypotony and associated hypotony maculopathy, bleb leak, transient choroidal effusion, device iris touch or dislocation into the anterior chamber, 23 shallow anterior chamber requiring reformation, and endophthalmitis. 21 The implant is inserted at the limbus under a scleral flap, without excision of the corneoscleral tissue block and iridectomy, and diverts the aqueous humor from the anterior chamber to the episcleral space, forming a conjunctival filtration bleb, similar to trabeculectomy.…”
mentioning
confidence: 99%
“…18,19 Because the conjunctiva alone is insufficient to control the initial aqueous flow during the early postoperative period, implantation under a scleral flap is currently recommended to prevent conjunctival erosion and to increase resistance to aqueous outflow in the immediate postoperative period. 20 Despite a number of studies that support the safety and efficacy of the subscleral technique, 21,22 complications include hyphema, transient hypotony and associated hypotony maculopathy, bleb leak, transient choroidal effusion, device iris touch or dislocation into the anterior chamber, 23 shallow anterior chamber requiring reformation, and endophthalmitis. 21 The implant is inserted at the limbus under a scleral flap, without excision of the corneoscleral tissue block and iridectomy, and diverts the aqueous humor from the anterior chamber to the episcleral space, forming a conjunctival filtration bleb, similar to trabeculectomy.…”
mentioning
confidence: 99%
“…There is a previous report of dislocation into the anterior chamber only in the early postoperative period, explained by the use of a wider-gauge needle to perforate the anterior chamber, the early laser suture lysis, and bleb massage; all of these factors may have contributed to migration of the external surface plate of the EX-PRESS implant. 4 In our case, the dislocation of the EX-PRESS after PET-CT was probably coincidental, because there was not documented exposure to a magnetic field, and a PET-MR or MRI was ruled out. Also, the patient had routine PET-CT scans every 6 months.…”
Section: Late-onset Spontaneous Ex-press Shunt Dislocation Into Anterior Chambermentioning
confidence: 69%
“…A 25-gauge needle track for the newer P series shunts is required, because of the slightly squared off shape. EX-PRESS glaucoma shunt dislocation into the anterior chamber has been described by Teng et al twenty-one days after the procedure with no evidence of corneal decompensation [24]. Moreover, Song et al recently reported a case of impending extrusion, due to previous improper spur fixation, treated by shunt-position adjustment [25].…”
Section: Ex-press Shunt Malpositionmentioning
confidence: 99%